Epidemiological Characteristics and Maternal Risk Factors of Microtia and Aural Atresia in Kazakhstan - Assel Imangaliyeva; Rimma Suatbayeva; Tatyana Slazhneva; Aigul Medeulova; Zhanetta Mukanova; Amangeldy Kulimbetov; Neilya Mileshina; Natalya Glushkova; Marina Izmailovich; Yuliya Semenova (International Archives of Otorhinolaryngology)
Introduction Microtia and aural atresia present congenital ear anomalies that affect external ear and are associated with conductive hearing loss. Both anomalies result from exposure to various prenatal risk factors, most common during the first trimester of pregnancy.